Splitting the Bill for Mobile Data with SIMlets - Raj, Himanshu; Saroiu, Stefan; Wolman, Alec; Padhye, Jitu (ACM HotMobile, 2013)
The scarcity of mobile broadband spectrum is a problem hurting all stakeholders in the mobile landscape – mobile operators (MOs), content providers, and mobile users. Building additional capacity is expensive, and MOs are reluctant to make such investments without a clear way of recouping their costs. This paper presents the idea of split billing: allowing content providers to pay for the traffic generated by mobile users visiting their websites or using their services. This creates an additional revenue stream for MOs and builds more pressure for updating their networks' capacities. End users also benefit because they can afford more expensive data plans and enjoy new applications and scenarios that make use of faster mobile networks. To implement split billing securely on a mobile platform, we develop the SIMlet, a new trustworthy computing abstraction. A SIMlet can be bound to a network socket to monitor and account all the traffic exchanged over the network socket. SIMlets provide trustworthy proofs of a device's mobile traffic, and such proofs can be redeemed at a content provider involved in split billing.